SP0065 To taper or not to taper non biological dmards in ra remission?. (12th June 2018) - Baker, K.F.; Isaacs, J.D.
Abstract : Remission is now a realistic goal in rheumatoid arthritis (RA), with a third of patients achieving sustained remission through the use of conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) in modern treat-to-target strategies. Nevertheless, csDMARDs pose a risk of severe side-effects and require regular blood safety monitoring, which is both intrusive for patients and expensive for healthcare systems. This poses a therapeutic challenge – when is it appropriate to withdraw csDMARDs from patients with RA in sustained disease remission? In the first part of this presentation we will use case histories to contrast the possible outcomes following withdrawal of csDMARDs from patients in sustained remission, highlighting the uncertainty facing patients and their clinicians in this scenario (presented by Dr Kenneth Baker). In the second section of this lecture (presented by Prof John Isaacs) we will discuss the criteria to consider when stopping csDMARDs, any potential risks to the strategy, and the potential to identify informative biomarkers to help guide management of the patient in remission. Disclosure of Interest: None declared